Effect of Inflation and BI Rate on Murabahah Financing in PT. Bank Syariah Indonesia - Nurfitriani; Rizaldi, Moh; Tanyong, A-aeso (Jeksyah: Islamic Economics Journal, 2022)
This study uses a quantitative approach, the population of this study is all reports of murabahah financing in 2016-April 2021, the instrument used is documentation. The results of this study indicate that partially inflation has no significant effect on Murabahah Financing for the period 2016 to April 2021. The Tcount value of inflation is smaller than Ttable (-0.986 <2.017) and a significance value greater than a (0.05) indicates that inflation does not have a significant effect on Murabahah Financing in the period 2016 to April 2021, and the BI Rate does not have a significant effect on Murabahah Financing for the period 2016 to April 2021, this is proven by the Tcount value of inflation which is smaller than the Ttable value (1.734<2.017) and the significance value which is greater than a (0.05) i.e. (0.088>0.05) indicates that the BI Rate has no significant effect on Murabahah Financing in the 2016 – April 2021 period. Simultaneously or together, Inflation and the BI Rate have a significant positive effect. on Murabahah Financing for the period 2016 to April 2021. The magnitude of the influence of Inflation and the BI Rate is together with Murabahah Financing, the coefficient of determination (Adjusted R) is 0.88 or 88%, while the remaining 12% is explained by other variables not examined in this study.